Advances in Autonomous Robotics Joint Proceedings of the 13th Annual TAROS Conference and the 15th Annual FIRA RoboWorld Congress, Bristol, UK, August 20-23, 2012 - Herrmann, Guido; Studley, Matthew; Pearson, Martin; Conn, Andrew; Melhuish, Chris; Witkowski, Mark.; Kim, Jong-Hwan.; Vadakkepat, Prahlad; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book constitutes the refereed proceedings of the 13th Conference on Towards Autonomous Robotic Systems, TAROS 2012 and the 15th Robot World Congress, FIRA 2012, held as joint conference in Bristol, UK, in August 2012. The 36 revised full papers presented together with 25 extended abstracts were carefully reviewed and selected from 89 submissions. The papers cover various topics in the field of autonomous robotics.
Keywords: Computer science; Data mining; Artificial intelligence; Computer vision; Computer Science; Artificial Intelligence (incl. Robotics).; Image Processing and Computer Vision; User Interfaces and Human Computer Interaction; Data Mining and Knowledge Discovery